Effect of Storage Time and Temperature for Maximum Bacteriocin Production by Lactic Acid Bacteria - Sumathi, V (International Journal of Pharmaceutical & Biological Archive, 2012)
Effect of Storage Time and Temperature for Maximum Bacteriocin Production by Lactic Acid Bacteria